Collaborative Governance Pemerintah Desa, Lembaga Adat dan Masyarakat Dalam Melestarikan Gawai Dayak - basel, BASELIUS AFRENDI; Widayanti , Sri (Journal of Indonesian Rural and Regional Government, 2025)
Over time, the implementation and function of Gawai Dayak have evolved due to population growth and increasing social diversity in terms of ethnicity, culture, religion, occupation, and other factors. Several issues have emerged, such as the perception that Gawai Dayak is a financial burden, the younger generation viewing it merely as entertainment with little cultural significance, conflicts during the celebration, and limited transparency and accountability in managing funds. This study uses a narrative qualitative method, focusing on Gawai Dayak as the research object, with village governments, traditional institutions, and local communities as subjects. Conducted in Umin Jaya Village, Dedai District, Sintang Regency, the study collected data through observation, interviews, and documentation, followed by stages of data reduction, presentation, and conclusion. The findings reveal that Gawai Dayak holds strong cultural value, including rituals like ngamik semengat padi, symbolizing hopes for a prosperous harvest, and ngemaik anak manik ke pian, a ritual of prayer and the lifting of taboos. The festival also fosters family gatherings and communal entertainment. Elements of collaborative governance are evident through formal interactions in organizing committees and informal discussions among members. Trust is built during the committee selection process and maintained throughout the planning, execution, and evaluation stages.